PENGEMBANGAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH DASAR BERBASIS KEMITRAAN DAN KEPEMIMPINAN TRANSFORMASIONAL DI KECAMATAN TALANG - Muhammad Mirwan; Beni Habibi; Yoga Prihatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Background: The demands of the Merdeka Belajar policy and the dynamics of 21st-century education necessitate the transformation of elementary school principals' roles from administrators to transformational leaders with managerial competence and the ability to build strategic partnerships. However, preliminary studies and performance reports in Talang District reveal competency gaps, particularly in human resource development, intellectual stimulation, and sustainable partnerships. Research Gap: Previous studies tended to analyze transformational leadership, managerial competence, and partnerships separately. Furthermore, integrative development models that are contextual for elementary school principals in semi-rural areas like Talang are still limited. Novelty of the Research: This research responds to this gap by developing and testing the validity of the ADAPT Model (Analysis-Design-Action-Partnership-Transformation), a holistic development model that is the first to integrate these three constructs into a synergistic framework adapted to the local context. Methods: The research used the Research and Development (R&D) method with the ADDIE model focused on the development stage. Data were collected through questionnaires (44 managerial items, 35 transformational items, 25 partnership items), interviews, and observations involving 10 principals and 10 teachers in Talang District. Product validity was tested through expert judgment (material, media, vocational experts) and pilot testing. Results: Needs analysis confirmed the existing conditions: managerial competence in the